2011
DOI: 10.1530/joe-11-0213
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induces adult human islet cell dedifferentiation

Abstract: Given the inherent therapeutic potential of the morphogenetic plasticity of adult human islets, the identification of factors controlling their cellular differentiation is of interest. The epidermal growth factor (EGF) family has been identified previously in the context of pancreatic organogenesis. We examined the role of EGF in an in vitro model whereby adult human islets are embedded in a collagen gel and dedifferentiated into duct-like epithelial structures (DLS). We demonstrated that DLS formation was EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…EGF plays an important role in the regulation of cell growth, proliferation and differentiation [20] and promotes epithelial proliferation in adult gut [21]. The potential value of using EGF as a therapeutic tool to treat gastrointestinal injury has been raised previously by some investigators [10] [22].…”
Section: Discussionmentioning
confidence: 99%
“…EGF plays an important role in the regulation of cell growth, proliferation and differentiation [20] and promotes epithelial proliferation in adult gut [21]. The potential value of using EGF as a therapeutic tool to treat gastrointestinal injury has been raised previously by some investigators [10] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increase in VEGF level and amounts of blood vessels, the extract of mushroom further led to increase in epidermal growth factors, proliferative cells (i.e., PCNA reaction), and collagen fibers as evident by Sirius red staining; and at the same time, a decrease of TUNEL positive apoptotic cells. Epidermal growth factor was known to increase the proliferation of cells, particularly the dedifferentiated ones (Hanley et al,2011). In this study, the increase of positive EGF sites was found on the epidermis, pointing to increase in proliferation of epidermal cells during healing after addition of this mushroom complex.…”
Section: Discussionmentioning
confidence: 99%
“…EGF is a growth factor that plays an important role in the regulation of cell growth, proliferation, and differentiation by binding to its receptor. Both epidermal growth factor receptor (Hanley et al,2011) and PCNA (Wai et al,2008) are proliferation markers.…”
Section: Methodsmentioning
confidence: 99%
“…Dedifferentiation and cell division are important intermediate processes in the process of switching phenotype, although they do not appear to be obligatory in all cases. Studies on the role of retinoblastoma protein (RB) and RB-like 2 showed that dedifferentiation of mature cardiomyocytes facilitated cardiomyocyte proliferation in cardiac hypertrophy [18] . Furthermore, inhibition of the p38 mitogen-activated protein kinase induced mammalian cardiomyocytes to dedifferentiate, which may be essential for cardiomyocyte regeneration [19,20] .…”
Section: Dedifferentiationmentioning
confidence: 99%